L’Angleterre et la Scandinavie : de l’histoire des femmes à l’histoire du genre - Sari Katajala-Peltomaa (Genre & Histoire)
The evolution of historiography has been more or less similar in England and in Scandinavian countries. The researchers have adopted the concepts and theories of scholars from the United States. The main difference between England and Scandinavian countries is undoubtedly the bigger quantity of scholars and variety of themes studied in England. The basic trend in England is the shift from the history of women to gender history while in the Scandinavian countries both lines of scholarship are still present. An important tendency in the English scholarship is the study of the interconnection between masculinity, femininity and sexuality. These themes have often been inspired by post-modern literature theories. These themes are not well represented in Scandinavian scholarship where economic and politic topics are the most numerous. The lack of available sources has also guided the interests of scholars in Finland and in Scandinavian countries.